Development of the Dangerous Road Maze Game to Stimulate Critical Thinking Abilities in Children Aged 5-6 Years - Haq, Azizah Ulfah; Sutama, I Wayan; Anisa, Nur; Putra, Yudithia Dian (Universitas Negeri Malang, 2024)
Technological developments can make learning more interesting and varied. In addition, children's development components will increase faster than before. Dangerous Road is an application-based game where players must complete road-finding missions by composing meaningful words that are relevant to the game theme. The ADDIE development model was used to develop the digital maze game “Dangerous Road”. This research uses a Likert scale questionnaire filled out by material experts, media experts and teachers, using qualitative and quantitative data analysis techniques. According to research and development results, the Maze Dangerous Road game is an effective, efficient and interesting learning medium for children aged 5 to 6 years. Small group trials were carried out on 5 children at Dharma Wanita Kencong 2 Kindergarten, with an effectiveness value of 80%, attractiveness 77.5%, and efficiency 72%; Large group trials were carried out on 28 children at the Dharma Wanita Kencong 2 Kindergarten with a total of 8 children and the Elbaith Rif'a Islamic Happy School Kindergarten with a total of 20 children, with an effectiveness score of 95%, attractiveness of 88.2%, and efficiency of 81.7%. Keywords: Early Childhood; Digital Maze Games; Critical Thinking